THE USE OF ROSETTA STONE SOFTWARE IN SPEAKING CLASS - Nanda Canita Putri; Sri Handayani (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2019)
Speaking is one of productive skills in which it used to comunicate with others. Speaking is so much a part of daily life that we take it for granted. Average person produces tens of thousands of words in a day. The aims of this study were to know whether Rosetta Stone software can improve students speaking skill and to show the class condition during this softwrare was implemented in teaching learning process for second grade students of SMP N 7 Surakarta 2017/2018 Academic Year. The method of the study was classroom action research and it is implemented on August 2018. To collect the data, there are 2 cycles. Each cycle used the test (oral test) and also non-test (observation, interview and documentation) .While, to analyze the data was used t-test. The result of this study showed that the implementation of Rosetta Stone software was succsessfully improve students’ speaking skill. pre-test and post test 1 was 58,12. meanwhile in the post-test 1 of cycle, it increased to 69. In the post-test 2 of cycle 2 had increased to the average value 76,12. To try the significance of teaching learning speaking result in first and second cycle, it was used t-test. The result was compared with the d.b= n- 1 30-1= 29, which showed in the table values, the table significance 5% was 2,045 and significance 1% was 2,756 the t-test score between pre-test and post-test 1 increased. It could be seen from the table values (2,045< 11,12 > 2,756), while t-test between post-test 1 and 2 also in creased. It can be seen from the table value (2,045< 7,06 > 2,756). It can be conclude that Rosetta Stone software was appropriate to improve students’ speaking skill in teaching learning process. Keywords: Rosetta Stone Software, Action Reseach, Speaking Skill.